Transcriptome-wide identification of the WUSCHEL-related homeobox transcription factors and their expression patterns underlying drought and salt stress in Populus euphratica - Ndayambaza, Boniface; Si, Jianhua; Zhao, Xin; Zhao, Yingxue; Zhou, Dongmeng; Jia, Bing; Liu, Zijin; Bai, Xue; Wang, Boyang (Frontiers in Plant Science, 2026)
Drought and salinity are major abiotic stresses that severely affect plant growth and the productivity of woody plants. The WUSCHEL-related homeobox (WOX) transcription factors are central to the regulation of plant development and plant stress responses, yet their roles in the stress-resilient desert tree Populus euphratica remain unexplored. Here we performed a genome-wide study to identify and characterize the WOX gene family of P. euphratica species. A total of 18 PeuWOX genes were discovered and characterized phylogenetically as modern, intermediate, and ancient clades. Members within each clade exhibited strong conservation in gene structure and protein motifs. Promoter analysis revealed a significant enrichment of stress- and hormone-responsive cis-elements. The 10 chosen PeuWOX genes were found to be differentially regulated by drought and salt stress in a tissue-specific manner by expression patterns through qRT-PCR. In leaves, PeuWOX1, PeuWOX2, PeuWOX4, and PeuWOX5 genes were sharply downregulated under salt stress, while PeuWOX9, PeuWOX10, and PeuWOX17 genes were significantly upregulated during prolonged drought or salt exposure. In roots and stems, PeuWOX5 and PeuWOX10 genes were induced rapidly, which may lead to a process of adaptation such as adventitious rooting, but PeuWOX4 and PeuWOX17 were induced over the long term associated with the development of the vascular system and long-term acclimation. Our results provided evidence that the PeuWOX family participates in a refined regulatory network, which fine-tunes stem, root, and leaf development with response to abiotic stress. This study provides an important background to the molecular mechanisms of the exceptional resistance to stress across P. euphratica and provides candidate genes to improve the stress tolerance of woody plants.